Pengaruh E-Trust, E-Satisfaction dan Perceived Value terhadap Repurchase Intention pada Konsumen E-Commerce B2C Coffee Shop - Kristin, Nadila Ivanka; Arafah, Willy (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study shows that e-trust, e-satisfaction, and perceived value significantly influence repurchase intention among B2C e-commerce coffee shop consumers. These findings underscore the importance of considering aspects of trust, satisfaction, and perceived value in the context of online shopping. With the positive relationship between these variables and repurchase intention, business managers can enhance their marketing strategies and services to increase customer loyalty. Additionally, this research highlights the crucial role of prior online experience as a moderator in the relationship between e-trust, e-satisfaction, perceived value, and repurchase intention. This indicates that previous online shopping experiences affect the extent to which these factors interact and impact consumers' decisions to repurchase. Therefore, business managers need to consider consumers' prior online experiences when designing effective marketing strategies. The results of this study are as follows: E-Trust positively influences Repurchase Intention, E-Satisfaction positively influences Repurchase Intention, Perceived value positively influences Repurchase Intention, E-Trust does not positively influence Repurchase Intention when moderated by Prior Online Experience, E-Satisfaction positively influences Repurchase Intention when moderated by Prior Online Experience, Perceived value does not positively influence Repurchase Intention when moderated by Prior Online Experience.